2021
DOI: 10.20990/kilisiibfakademik.969504
|View full text |Cite
|
Sign up to set email alerts
|

Dijital Bağımlılık ile Yaratıcı Düşünme Eğilimi Arasındaki İlişkinin İncelenmesi: Üniversite Öğrencileri Üzerine Bir Araştırma

Abstract: Bu araştırmanın amacı, üniversite öğrencilerinin dijital bağımlılık düzeyleri ve yaratıcı düşünme eğilimlerini ve aralarındaki ilişkileri çeşitli değişkenler itibariyle incelenmektir. Purpose:The purpose of this research is to examine the digital addiction levels and creative thinking tendencies of university students and the relationships between them in terms of various variables. Tasarım/Yöntem: Araştırmada tesadüfi olmayan yöntemlerden kolayda örneklem yöntemiyle belirlenen 400 katılımcı ile yüz yüze anket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…When the literature is reviewed, many studies on digital addiction (Altınok, 2021;Arseven, 2020;Arslan, 2019;Arslan, 2020a;Arslan, 2020b;Arslan & Bardakçı, 2020;Arslan & Bardakçı, 2021;Arslan, Kırık, Karaman and Çetinkaya, 2015;Dilci, Arslan, & Ersoy, 2019;Eryılmaz & Çukurluöz, 2018;Kanter, 2020;Koç & Yıldız, 2021;Taşlıyan, Karakuş, & Çakıroğlu, 2021;Yalçın, 2021) focused mainly on secondary and high school levels, and No study has been found to directly determine the digital addiction levels of Turkish teacher candidates. In this study, it was aimed to examine the digital addiction levels of Turkish teacher candidates in terms of different variables.…”
Section: Extended Abstractmentioning
confidence: 99%
See 1 more Smart Citation
“…When the literature is reviewed, many studies on digital addiction (Altınok, 2021;Arseven, 2020;Arslan, 2019;Arslan, 2020a;Arslan, 2020b;Arslan & Bardakçı, 2020;Arslan & Bardakçı, 2021;Arslan, Kırık, Karaman and Çetinkaya, 2015;Dilci, Arslan, & Ersoy, 2019;Eryılmaz & Çukurluöz, 2018;Kanter, 2020;Koç & Yıldız, 2021;Taşlıyan, Karakuş, & Çakıroğlu, 2021;Yalçın, 2021) focused mainly on secondary and high school levels, and No study has been found to directly determine the digital addiction levels of Turkish teacher candidates. In this study, it was aimed to examine the digital addiction levels of Turkish teacher candidates in terms of different variables.…”
Section: Extended Abstractmentioning
confidence: 99%
“…Literatür taraması yapıldığında dijital bağımlılığa yönelik pek çok çalışmanın (Altınok, 2021;Arseven, 2020;Arslan, 2019;Arslan, 2020a;Arslan, 2020b;Arslan & Bardakçı, 2020;Arslan & Bardakçı, 2021;Arslan, Kırık, Karaman, & Çetinkaya, 2015;Dilci, Arslan, & Ersoy, 2019;Eryılmaz & Çukurluöz, 2018;Kanter, 2020;Koç & Yıldız, 2021;Taşlıyan, Karakuş, & Çakıroğlu, 2021;Yalçın, 2021) gerçekleştirildiği, çalışmalarda ağırlıklı olarak ortaokul ve lise düzeyine odaklanıldığı görülmüş ve doğrudan Türkçe öğretmen adaylarının dijital bağımlılık düzeylerini belirlemeye yönelik herhangi bir çalışmaya rastlanmamıştır. 21.…”
unclassified